Challenges associated with teaching interdisciplinary courses - Getting the level right and increasing student’s active participation in classes - Bech Bruun, Thilde (Improving University Science Teaching and Learning, 2023)
During the last four years, I have been teaching on two interdisciplinary Master’s level courses (’Tropical Crop Production’ and ’Thematic Course in Interdisciplinary Land Use and Natural Resource Management’) that are both hosted at Department of Plant and Environmental Sciences. Both courses are followed by students with very diverse disciplinary backgrounds. My experiences from teaching these two courses have made me reflect on the challenges associated with interdisciplinary teaching in an international context and encouraged me to experiment with methods to overcome these challenges. This project takes point of departure in the challenges that I have faced while teaching the course in Tropical Crop Production and describes and discusses the measures that I have applied in attempt to overcome these challenges.